A novel Strain-Energy-Density based fatigue criterion accounting for mean stress and plasticity effects on the medium-to-high-cycle uniaxial fatigue strength of plain and notched components. (April 2020) - Benedetti, M.; Berto, F.; Le Bone, L.; Santus, C.
Graphical abstract: Highlights: Mean stress and plasticity effects are included into a novel fatigue criterion. This is based on the definition of 4 elastic and plastic components of SED. Stabilization of the elastic-plastic response is investigated. Criterion parameters are calibrated from experimental fatigue data. Very accurate prediction of independent fatigue data. Abstract: A novel strain-energy–density (SED) based fatigue criterion is here proposed to account for the effect of mean stress and plasticity on the uniaxial fatigue strength of plain and notched components. It is based on the definition of four SED components: Δ W ¯ el, the elastic SED associated to the stress range, Δ W ¯ el, max, the maximum elastic SED in the stabilized cycle, Δ W ¯ pl, the plastic SED dissipated per stabilized cycle, W ¯ pl, max, the plastic SED dissipated over the cycles until stabilization. The mean stress effect is incorporated in a Walker-like expression, Δ W ¯ el α W ¯ el, max 1 - α, while W ¯ pl, max is added to the expression of the total SED to include the effect of mean stress relaxation. An energetic approach is proposed to identify the condition of cycle stabilization. The coefficients of the fatigue criterion are calibrated using experimental fatigue data. The criterion is validated by predictions of independent data.